2023
DOI: 10.1007/s10552-023-01691-1
|View full text |Cite
|
Sign up to set email alerts
|

The special sauce of the Cancer Prevention and Control Research Network: 20 years of lessons learned in developing the evidence base, building community capacity, and translating research into practice

Abstract: Purpose The Cancer Prevention and Control Research Network (CPCRN) is a national network focused on accelerating the translation of cancer prevention and control research evidence into practice through collaborative, multicenter projects in partnership with diverse communities. From 2003 to 2022, the CPCRN included 613 members. Methods We: (1) characterize the extent and nature of collaborations through a bibliometric analysis of 20 years of Network public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Qualitative interview findings are presented according to the four thematic content categories identified ( Mohile et al, 2018 ): purpose and value of a CGA and how this is communicated to patients and families ( Leeman et al, 2019 ), CGA administration logistics ( Wheeler et al, 2023 ), barriers and facilitators to CGA implementation, and ( White et al, 2019 ) implementation training preferences and needs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Qualitative interview findings are presented according to the four thematic content categories identified ( Mohile et al, 2018 ): purpose and value of a CGA and how this is communicated to patients and families ( Leeman et al, 2019 ), CGA administration logistics ( Wheeler et al, 2023 ), barriers and facilitators to CGA implementation, and ( White et al, 2019 ) implementation training preferences and needs.…”
Section: Resultsmentioning
confidence: 99%
“…Functional status 5 IDLs/IADLs (Wheeler et al, 2023); Observation (Mohile et al, 2018); SF36 (Mohile et al, 2018) Cognition 6 Mini-Cog (Leeman et al, 2019); MMSE (Mohile et al, 2018); Mini-Cog/MOCA (Mohile et al, 2018); PROMIS (Mohile et al, 2018); Blessed Test, then MOCA (Mohile et al, 2018) Depression 6 Geriatric Depression Scale (Wheeler et al, 2023); PROMIS (Mohile et al, 2018); GDS as part of SAOP (Mohile et al, 2018); Screening questionnaire (Mohile et al, 2018) Nutrition 5 Mini Nutrition Assessment (Wheeler et al, 2023); BMI calculation (Mohile et al, 2018); Patient Generated Subject Global Assessment (Mohile et al, 2018) Gait and balance 6 Clinic question (Mohile et al, 2018); Performance battery (Mohile et al, 2018); Short Physical Performance Battery and grip strength (Mohile et al, 2018); Short Physical Performance Battery (Mohile et al, 2018); Observation (Mohile et al, 2018); Fall history (Mohile et al, 2018) Cumulative illness rating 2 Considered part of comorbidity (Mohile et al, 2018); "specific calculator" (Mohile et al, 2018) Comorbidities 6 Geriatric-specific Comorbidity Index (Wheeler et al, 2023); Charleston Comorbidity Index (Leeman et al, 2019); Chart review (Mohile et al, 2018) Quality of life 4 Considered advanced care planning discussion (Mohile et al, 2018); PROMIS Global-10 (Mohile et al, 2018); SAOP3 (Mohile et al, 2018); Self-reported quality of life (Mohile et al, 2018) Frontiers in Aging frontiersin.org So a geriatric assessment which is a multidimensional evaluation of a number of domains that a regular oncologist normally will not evaluate, that assessment allows you to. .…”
Section: Cga Domains # Providers Assessing Each Domain Assessment Too...mentioning
confidence: 99%
See 2 more Smart Citations